Pengaruh Kualitas Layanan Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Mediasi - Abdul Azis; Esti Dwi Rahmawati; Khabib Alia Akhmad (Universitas Katolik Widya Karya Malang, 2023)
The development of the business world is currently experiencing quite high development, not only in the manufacturing industry but many are entering the world of service markets, by presenting similar or even the same service products, thus making service businesses compete to provide service quality and satisfaction in order to gain customer loyalty. . This study aims to analyze the effect of service quality on customer loyalty through customer satisfaction as a mediating variable. Samples were taken using a non-probability sampling technique with a purposive sampling technique with the criteria of consumers who had ordered more than 3 times which resulted in a sample of 90 people, the method of data collection was through distributing google form questionnaires with a Likert scale of 1-5 as a measuring tool. Data analysis techniques in this study used simple linear analysis and partial regression test (t test). Data processing was carried out using the SPSS 25 program. The results of this study indicated that service quality had a significant effect on customer loyalty, service quality had a significant effect on customer satisfaction, customer satisfaction had a significant effect on customer loyalty, and customer satisfaction was proven to mediate the effect of service quality on consumer loyalty.